A deep ultraviolet AlGaN-based multi-quantum well light emitting diode and a preparation method thereof
Patent Information
- Application Number
- CN202211496260.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-24
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2042-11-24
AI Technical Summary
进一步地,为了有效抑制电子泄漏,在深紫外LED中就必须采用Al组分极高的电子阻挡层(EBL),从而增大了材料的外延生长难度,并有可能产生大量的晶体缺陷,使得材料外延质量变差,器件内部非辐射复合过程增强,导致LED发光效率降低
[0029] A deep ultraviolet AlGaN/AlGaN multi-quantum-well light-emitting diode structure is proposed. An AlGaN composite barrier layer (CQB) is used to replace the last quantum barrier (LQB) and electron blocking layer (EBL) in the traditional LED, thereby eliminating the original heterojunction structure at the LQB/EBL interface, reducing the polarization effect in the whole structure, suppressing band bending, and thus improving the carrier transport efficiency.
Smart Images

Figure BDA0003962465050000051 
Figure BDA0003962465050000061 
Figure HDA0003962465060000011
Abstract
Description
Technical Field
[0001] This invention belongs to the field of semiconductor technology, specifically a deep ultraviolet AlGaN-based multi-quantum-well light-emitting diode and its fabrication method. Background Technology
[0002] AlGaN materials primarily emit light in the ultraviolet (UV) band, ranging from 200 nm to 365 nm. Due to the wide applications of UV light in water disinfection, medical device sterilization, UV therapy, document verification, and encrypted communication, AlGaN-based group III nitride UV light-emitting diodes (LEDs) have attracted increasing attention. Compared to blue-green LEDs, deep UV LEDs generally have lower quantum efficiency and luminous power. This is mainly because to achieve short-wavelength emission in the deep UV, the quantum well of the LED must be made of AlGaN material, requiring a higher Al content AlGaN layer as the quantum barrier layer. Furthermore, to effectively suppress electron leakage, a very high Al content electron blocking layer (EBL) must be used in deep UV LEDs, increasing the difficulty of epitaxial growth and potentially generating numerous crystal defects. This leads to poor epitaxial quality, enhanced non-radiative recombination within the device, and ultimately, reduced LED luminous efficiency. On the other hand, the extremely high Al content in the electron-blocking electron (EBL) negatively impacts hole transport, reducing hole injection efficiency and decreasing hole concentration in the active region, further deteriorating the luminous performance of deep ultraviolet (DUV) LEDs. Therefore, improving the electron blocking capability to effectively suppress electron leakage, while simultaneously improving hole injection efficiency, will be a key factor in enhancing the overall performance of AlGaN-based DUV LED devices. Summary of the Invention
[0003] To overcome the shortcomings of traditional deep ultraviolet light-emitting diodes (DUVs) in terms of low quantum efficiency and low luminous power, this invention proposes a deep ultraviolet AlGaN-based multi-quantum-well LED and its fabrication method.
[0004] The technical solution adopted by this invention to solve its technical problem is:
[0005] A deep ultraviolet AlGaN-based multi-quantum-well light-emitting diode mainly includes a substrate, an AlN intrinsic layer, an N-type AlGaN template layer, a multi-quantum-well active region, an AlGaN composite barrier layer, a P-type AlGaN capping layer, a P-type GaN ohmic contact layer, an N-type ohmic electrode, and a P-type ohmic electrode.
[0006] The diode has a layered structure, with the substrate at the bottom and the P-type GaN ohmic contact layer at the top.
[0007] From bottom to top, the layers are: an intrinsic AlN layer, an N-type AlGaN template layer, a multi-quantum-well active region, an AlGaN composite barrier layer, and a P-type AlGaN capping layer, with each layer connected sequentially.
[0008] The AlN intrinsic layer is grown on the underlying substrate, the N-type AlGaN template layer is grown on the AlN intrinsic layer, and so on.
[0009] In the N-type AlGaN template layer, steps are provided. The step surfaces are parallel to the layers that make up the diode. The upper step surface is connected to the active region of the multi-quantum well, and the lower step surface is connected to the N-type ohmic electrode.
[0010] The P-type ohmic electrode is located on the upper side of the P-type GaN ohmic contact layer.
[0011] The substrate material is sapphire.
[0012] The intrinsic AlN layer is grown on the substrate with a thickness of 500–1000 nm.
[0013] The N-type AlGaN template layer is grown on the intrinsic AlN layer, with a thickness of 2–4 μm. In the N-type AlGaN template layer, Si is used as the n-type dopant, with a doping concentration of not less than 1 × 10⁻⁶. 18 cm -3 .
[0014] The multi-quantum-well active region is grown on an N-type AlGaN template layer. The quantum well layer in the multi-quantum-well active region is an AlGaN layer with a thickness of 3-4 nm. The quantum barrier layer is an AlGaN layer with an Al composition higher than that in the quantum well, and its thickness is 10-15 nm. The number of repetition periods for the alternating growth of AlGaN quantum wells and AlGaN quantum barriers is not less than 2.
[0015] The AlGaN composite barrier layer is grown on the multi-quantum-well active region, with a thickness of 20-30 nm, while satisfying the condition that it is not less than twice the thickness of the quantum barrier layer in the multi-quantum-well active region. The Al composition in the AlGaN composite barrier layer gradually decreases along the epitaxial growth direction. Mg is used as a p-type dopant in the AlGaN composite barrier layer, and doping is performed in regions far from the quantum wells, ensuring that the thickness of the doped region is equal to the total thickness of the AlGaN composite barrier layer minus the thickness of the quantum barrier layer in the multi-quantum-well active region, with a doping concentration of not less than 1 × 10⁻⁶. 19 cm -3 .
[0016] A p-type AlGaN capping layer with a linearly graded Al composition and a thickness of 50–100 nm is grown on an AlGaN composite barrier layer. In the AlGaN capping layer, Mg is used as the p-type dopant with a doping concentration of not less than 2 × 10⁻⁶. 19 cm -3 .
[0017] The p-type GaN ohmic contact layer is grown on a p-type AlGaN capping layer, with a thickness of 100–300 nm, using Mg as the p-type dopant with a doping concentration of not less than 2 × 10⁻⁶. 19 cm -3 .
[0018] The N-type ohmic electrode is a dot-like structure, deposited on the steps of the etched N-type AlGaN template layer.
[0019] The P-type ohmic electrode has a dot-like structure and is deposited on a P-type GaN ohmic contact layer.
[0020] The substrate material of the aforementioned diode can also be SiC.
[0021] The substrate material of the aforementioned diode can also be AlN.
[0022] In the aforementioned diode, the N-type ohmic electrode can also be a ring structure.
[0023] In the aforementioned diode, the P-type ohmic electrode can also be a ring structure.
[0024] A method for fabricating a deep ultraviolet AlGaN-based light-emitting diode includes the following steps:
[0025] Step 1: Take a substrate, the material of which is sapphire, SiC or AlN.
[0026] Step 2: Grow the following layers sequentially on the substrate: an intrinsic AlN layer, an N-type AlGaN template layer, a multi-quantum-well active region, an AlGaN composite barrier layer, a P-type AlGaN capping layer, and a P-type GaN ohmic contact layer.
[0027] Step 3: Form a mesa device structure through photolithography and etching processes, and deposit N-electrodes and P-electrodes on the N-type AlGaN template layer and the P-type GaN ohmic contact layer, respectively. Then, anneal and cool in a nitrogen atmosphere to complete the growth.
[0028] The beneficial effects of this invention are:
[0029] A deep ultraviolet AlGaN / AlGaN multi-quantum-well light-emitting diode structure is proposed. An AlGaN composite barrier layer (CQB) is used to replace the last quantum barrier (LQB) and electron blocking layer (EBL) in the traditional LED, thereby eliminating the original heterojunction structure at the LQB / EBL interface, reducing the polarization effect in the whole structure, suppressing band bending, and thus improving the carrier transport efficiency.
[0030] The structure of this invention uses an AlGaN-CQB layer to increase the effective barrier height of the conduction band, enhance the ability to block electrons, and allow more electrons to undergo radiative recombination in the active region, thereby improving the light-emitting performance of the device.
[0031] The structure of this invention, using an AlGaN-CQB layer, further reduces the effective barrier height of the valence band, improves hole injection, and enhances the light-emitting performance of the device.
[0032] Compared to the EBL in traditional LED structures, the average Al content in the AlGaN composite barrier layer of this invention is not increased; in fact, it can be lower. As is well known, extremely high Al content leads to an increase in total stress in the epitaxial material, which is a core challenge in the development of deep ultraviolet LEDs. Therefore, this invention helps to reduce the total stress in the entire LED structure, thereby reducing the difficulty of epitaxial growth of deep ultraviolet LEDs. Attached Figure Description
[0033] The present invention will be further described below with reference to the accompanying drawings and embodiments.
[0034] Figure 1 This is a schematic cross-sectional view of the light-emitting diode of the present invention;
[0035] Figure 2 This is a flowchart of a method for growing a deep ultraviolet AlGaN / AlGaN deep ultraviolet multi-quantum-well light-emitting diode according to the present invention.
[0036] Figure 3 This is a schematic diagram of the structure of the AlGaN composite barrier layer 5 in specific embodiment 1 of the present invention;
[0037] Figure 4 This is a schematic diagram of the structure of AlGaN composite barrier layer 5, which is a comparative example of the traditional structure.
[0038] Figure 5 This is a comparison chart of the internal quantum efficiency of a specific embodiment 1 of the AlGaN composite barrier layer of the present invention and a conventional structure.
[0039] Figure 6 This is a comparison chart of the optical output power of a specific embodiment 1 of the AlGaN composite barrier layer of the present invention and a conventional structure.
[0040] In the figure: 1. Substrate; 2. Intrinsic AlN layer; 3. N-type AlGaN template layer; 4. Multiple quantum well active region; 5. AlGaN composite barrier layer; 6. P-type AlGaN capping layer; 7. P-type GaN ohmic contact layer; 8. N-type ohmic electrode; 9. P-type ohmic electrode. Detailed Implementation
[0041] Examples 1, 2, and 3:
[0042] A deep ultraviolet AlGaN / AlGaN multi-quantum-well light-emitting diode mainly includes a substrate 1, an AlN intrinsic layer 2, an N-type AlGaN template layer 3, a multi-quantum-well active region 4, an AlGaN composite barrier layer 5, a P-type AlGaN capping layer 6, a P-type GaN ohmic contact layer 7, an N-type ohmic electrode 8, and a P-type ohmic electrode 9, as shown. Figure 1 As shown.
[0043] The diode has a layered structure, with substrate 1 at the bottom and P-type GaN ohmic contact layer 7 at the top.
[0044] From bottom to top, the layers are: AlN intrinsic layer 2, N-type AlGaN template layer 3, multi-quantum well active region 4, AlGaN composite barrier layer 5, and P-type AlGaN capping layer 6, with each layer connected sequentially.
[0045] AlN intrinsic layer 2 is grown on the underlying substrate 1, and N-type AlGaN template layer 3 is grown on AlN intrinsic layer 2, and so on.
[0046] In the N-type AlGaN template layer 3, a step is provided. The step surface is parallel to each layer that makes up the diode. The upper step surface is connected to the multi-quantum well active region 4, and the lower step surface is connected to the N-type ohmic electrode 8.
[0047] The P-type ohmic electrode 9 is located on the upper side of the P-type GaN ohmic contact layer 7.
[0048] The substrate 1 is made of sapphire, SiC, or AlN.
[0049] The AlN intrinsic layer 2 is grown on the substrate 1 with a thickness of a1.
[0050] The N-type AlGaN template layer 3 is grown on the intrinsic AlN layer 2, with a thickness of a2. In the N-type AlGaN template layer, the atomic percentage of Al is 50%, and Si is used as the n-type dopant with a doping concentration of 1 × 10⁻⁶. 18 cm -3 .
[0051] The multi-quantum-well active region 4 is grown on the N-type AlGaN template layer 3. The multi-quantum-well active region 4 comprises alternating quantum well layers and quantum barrier layers, wherein the quantum well layers have a thickness of a3 and are composed of Al with a composition of 47%. 0.47 Ga 0.53 N, the thickness of the quantum well barrier layer a4, and the composition is Al with a composition of 65% Al. 0.65 Ga 0.35 N. The number of repetition cycles for the alternating growth of quantum well layers and quantum barrier layers is s1.
[0052] The AlGaN composite barrier layer 5 is grown on the multi-quantum-well active region 4, with a thickness of a5, where a5 = a4 + a6. Here, a4 is the thickness of the quantum barrier layer in the multi-quantum-well active region 4, a6 is the thickness of the electron blocking layer in a conventional deep ultraviolet light-emitting diode, and a6 ≥ a4.
[0053] In the AlGaN composite barrier layer 5, the Al composition gradually decreases along the epitaxial growth direction, linearly decreasing from 85% to 65%. Mg is used as a p-type dopant in AlGaN composite barrier layer 5, and doping is performed on a region of thickness a6 far from the quantum well, with a doping concentration of 1×10⁻⁶. 19 cm -3 .
[0054] A p-type AlGaN capping layer 6 is grown on top of an AlGaN composite barrier layer 5 with a linearly graded Al composition, and the thickness is a7. The atomic percentage of Al in the p-type AlGaN capping layer 6 is 50%. Mg is used as the p-type dopant, with a doping concentration of 2 × 10⁻⁶. 19 cm -3 .
[0055] The p-type GaN ohmic contact layer 7 is grown on the p-type AlGaN capping layer 6, with a thickness of a8. Mg is used as the p-type dopant, with a doping concentration of 2 × 10⁻⁶. 19 cm -3 .
[0056] The N-type ohmic electrode 8 has a dot-like or ring-like structure and is deposited on the etched N-type AlGaN template layer 3.
[0057] The P-type ohmic electrode 9 has a dot-like or ring-like structure, and the P-type ohmic electrode 8 is deposited on the P-type GaN ohmic contact layer 7.
[0058] Table 1 shows some relevant parameters for Examples 1, 2, and 3.
[0059] Table 1 Relevant Parameters
[0060]
[0061]
[0062] Example 1: Comparison of preparation and performance with traditional structures:
[0063] Reference Figure 1 and Figure 2 This paper proposes a specific deep-ultraviolet AlGaN-based multi-quantum-well light-emitting diode structure and its fabrication method, including the following steps:
[0064] Step 1, Substrate processing
[0065] Take a substrate 1, the material of which is sapphire, SiC or AlN. Perform a high-temperature cleaning treatment on the substrate 1 at 1200°C in a hydrogen atmosphere for 5 to 20 minutes, and then perform a nitriding treatment.
[0066] Step 2, Growth of the substrate
[0067] Step 1: Growth of AlN intrinsic layer 2
[0068] An intrinsic AlN layer 2 is sequentially grown on substrate 1. First, a low-temperature buffer layer with a thickness of 50 nm is grown on the substrate within the intrinsic AlN layer at 600 °C. Then, the temperature is increased to 1400 °C, and a 550 nm intrinsic AlN layer is grown on the low-temperature buffer layer, resulting in a total intrinsic AlN layer thickness of 600 nm.
[0069] The second step is to grow an N-type AlGaN template layer 3 on the AlN intrinsic layer 2.
[0070] A 3 μm AlGaN template layer was grown on the intrinsic AlN layer at a growth temperature of 1200 °C, with an Al content of 50%. Si was used as the n-type dopant with a doping concentration of 1 × 10⁻⁶. 18 cm -3 .
[0071] The third step is to grow a multi-quantum-well active region 4 on the N-type AlGaN template layer 3.
[0072] Al was grown alternately for four cycles at 1000℃. 0.65 Ga 0.35 N / Al 0.47 Ga 0.53 N, where Al 0.65 Ga 0.35 The thickness of the N barrier is 10 nm, Al 0.47 Ga 0.53 The thickness of the N-well is 3 nm;
[0073] The fourth step is to grow an AlGaN composite barrier layer 5 on the multi-quantum-well active region 4.
[0074] Without changing the reaction chamber temperature, a 20 nm thick AlGaN linearly graded layer with an Al composition percentage linearly decreasing from 85% to 65% was directly grown. Mg was used as a p-type dopant to dope a 10 nm thick region far from the multi-quantum-well active region, with a doping concentration of 1 × 10⁴. 19 cm -3 The specific structure is as follows Figure 3 As shown;
[0075] Fifth step: Grow a P-type AlGaN capping layer 6 on the AlGaN composite barrier layer 5.
[0076] Without changing the reaction chamber temperature, a 50 nm thick AlGaN capping layer 6 was grown using Mg as a p-type dopant with a doping concentration of 2 × 10⁻⁶. 19 cm -3 .
[0077] Step 6: Growth of a p-type GaN ohmic contact layer 7
[0078] The reaction chamber temperature was lowered to 800℃, and a 100nm thick GaN contact layer 17 was regrown using Mg as a p-type dopant with a doping concentration of 2×10⁻⁶. 19 cm -3 .
[0079] Step 3: Process the worktable and deposit the electrode.
[0080] Mesa device structures are formed through photolithography and etching processes, and dot-structured N-type ohmic electrodes 8 and P-type ohmic electrodes 9 are deposited on the N-type AlGaN template layer 3 and the P-type GaN ohmic contact layer 7, respectively. Then, hot annealing alloying process is used to improve the ohmic contact characteristics and complete the device growth.
[0081] The structure of the diode in Example 1 is compared with that of existing diodes as follows:
[0082] In the traditional structure comparison example, based on the steps described above, only the growth steps of the AlGaN composite barrier layer 5 are changed, and instead a 10nm thick Al layer is grown first. 0.65 Ga 0.35 N quantum barrier layer, regrown with 10nm thick Al 0.85 Ga 0.15 An N-type electron blocking layer is formed, and the electron blocking layer is p-type doped with Mg at the same concentration as in Example 1 of this invention. Its specific structure is as follows: Figure 4 As shown.
[0083] The performance comparison test of the diode in Example 1 with existing diodes is as follows:
[0084] The photoelectric performance of the embodiments of the present invention was tested in comparison with that of the conventional structure. The present invention significantly improves the internal quantum efficiency and light output power of the deep ultraviolet AlGaN multi-quantum-well light-emitting diode. The comparison results are as follows: Figure 5 and Figure 6 As shown.
[0085] It should be noted that the above description is merely a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention shall fall within the scope of protection claimed by the present invention.
Claims
1. A deep ultraviolet AlGaN-based multi-quantum-well light-emitting diode, characterized in that, The main components include a substrate (1), an intrinsic AlN layer (2), an N-type AlGaN template layer (3), a multi-quantum well active region (4), an AlGaN composite barrier layer (5), a P-type AlGaN capping layer (6), a P-type GaN ohmic contact layer (7), an N-type ohmic electrode (8), and a P-type ohmic electrode (9). The diode has a layered structure, with the substrate (1) located at the bottom layer and the P-type GaN ohmic contact layer (7) located at the top layer; From bottom to top, the layers are: the AlN intrinsic layer (2), the N-type AlGaN template layer (3), the multi-quantum well active region (4), the AlGaN composite barrier layer (5), and the P-type AlGaN capping layer (6), which are connected one after another. The AlN intrinsic layer (2) is grown on the underlying substrate (1), and the N-type AlGaN template layer (3) is grown on the AlN intrinsic layer (2), and so on. In the N-type AlGaN template layer (3), a step is provided. The step surface is parallel to each layer that makes up the diode. The upper step surface is connected to the multi-quantum well active region (4), and the lower step surface is connected to the N-type ohmic electrode (8). The P-type ohmic electrode (9) is located on the upper side of the P-type GaN ohmic contact layer (7); The substrate (1) is made of sapphire. The intrinsic AlN layer (2) is grown on the substrate (1) and has a thickness of 500~1000nm; The N-type AlGaN template layer (3) is grown on the intrinsic AlN layer (2) and has a thickness of 2~4μm. In the N-type AlGaN template layer (3), Si is used as the n-type dopant and the doping concentration is not less than 1×10⁻⁶. 18 cm -3 The multi-quantum-well active region (4) is grown on the N-type AlGaN template layer (3). The quantum well layer in the multi-quantum-well active region (4) is an AlGaN layer with a thickness of 3-4 nm. The quantum barrier layer is an AlGaN layer with an Al composition higher than that in the quantum well, and a thickness of 10-15 nm. The number of repetition periods for the alternating growth of AlGaN quantum wells and AlGaN quantum barriers is not less than 2. The AlGaN composite barrier layer (5) is grown on the multi-quantum-well active region (4) with a thickness of 20-30 nm, while satisfying that it is not less than twice the thickness of the quantum barrier layer in the multi-quantum-well active region (4). The Al composition in the AlGaN composite barrier layer (5) gradually decreases along the epitaxial growth direction, with the Al composition linearly changing from 85% to 65%. Mg is used as a p-type dopant in the AlGaN composite barrier layer (5), and the region far from the quantum well is doped to ensure that the thickness of the doped region is equal to the total thickness of the AlGaN composite barrier layer (5) minus the thickness of the quantum barrier layer in the multi-quantum-well active region (4), and the doping concentration is not less than 1×10⁻⁶. 19 cm -3 ; The p-type AlGaN capping layer (6) is grown on an AlGaN composite barrier layer (5) with a linearly graded Al composition and a thickness of 50~100 nm; in the p-type AlGaN capping layer (6), Mg is used as a p-type dopant with a doping concentration of not less than 2×10⁻⁶. 19 cm -3 ; The p-type GaN ohmic contact layer (7) is grown on the p-type AlGaN capping layer (6) with a thickness of 100~300nm. Mg is used as the p-type dopant with a doping concentration of not less than 2×10⁻⁶. 19 cm -3 ; The N-type ohmic electrode (8) is a dot-like structure, deposited on the steps of the etched N-type AlGaN template layer (3); The P-type ohmic electrode (9) is a dot-like structure deposited on the P-type GaN ohmic contact layer (7).
2. The deep ultraviolet AlGaN-based multi-quantum-well light-emitting diode according to claim 1, characterized in that, The substrate (1) is made of SiC.
3. The deep ultraviolet AlGaN-based multi-quantum-well light-emitting diode according to claim 1, characterized in that, The substrate (1) is made of AlN.
4. The deep ultraviolet AlGaN-based multi-quantum-well light-emitting diode according to claim 1, characterized in that, The N-type ohmic electrode (8) has a ring structure.
5. The deep ultraviolet AlGaN-based multi-quantum-well light-emitting diode according to claim 1, characterized in that, The P-type ohmic electrode (9) has a ring structure.
6. A method for fabricating a deep ultraviolet AlGaN-based multi-quantum-well light-emitting diode according to any one of claims 1 to 5, characterized in that, Includes the following steps: Step 1: Take a substrate (1), the material of which is sapphire, SiC or AlN; Step 2: On the substrate (1), the intrinsic AlN layer (2), the N-type AlGaN template layer (3), the multi-quantum well active region (4), the AlGaN composite barrier layer (5), the P-type AlGaN capping layer (6), and the P-type GaN ohmic contact layer (7) are grown sequentially. Step 3: Form a mesa device structure through photolithography and etching processes, and deposit N-type ohmic electrodes (8) and P-type ohmic electrodes (9) on the N-type AlGaN template layer (3) and the P-type GaN ohmic contact layer (7), respectively. Then, anneal and cool in a nitrogen atmosphere to complete the growth.
Citation Information
Patent Citations
Polarity face GaN-based light-emitting device capable of improving light-emitting efficiency
CN103887385A
Epitaxial growth method for improving luminous efficiency of LED
CN103887392A
LED and preparation method thereof
CN105374912A
Ultraviolet semiconductor light-emitting device and method for manufacturing same
WO2022215876A1